2019
DOI: 10.1111/ina.12563
|View full text |Cite
|
Sign up to set email alerts
|

Direct or indirect exposure of exhaled contaminants in stratified environments using an integral model of an expiratory jet

Abstract: The risk of cross‐infection is high when the susceptible persons are exposed to the pathogen‐laden droplets or droplet nuclei exhaled by infectors. This study proposes a jet integral model to predict the dispersion of exhaled contaminants, evaluating the exposure risk and determining a threshold distance to identify the direct and indirect exposures in both thermally uniform and stratified environments. The results show that the maximum concentration of contaminants exhaled by a bed‐lying infector clearly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…However, in some indoor environments, such as buoyancy‐driven ventilated spaces with DV, 31,32 UFAD, 33,34 and/or NV, 35,36 the air temperature is vertically stratified because the low‐momentum air supply is attached to the floor, which is more likely to be seen in public places like shopping centers, railway waiting rooms, and the rebuilt Fangcang hospital. In such environments, the exhalation airflow and airborne pollutants were found to be easily trapped at a certain height and were able to penetrate a very long distance along the exhalation direction, which was referred to as the lock‐up phenomenon, as reported in previous studies 21,27,30,37,38 . Bjørn and Nielsen 17 observed that if the temperature gradient was sufficiently large, the lock‐up layer of the exhaled airborne pollutants could settle at breathing height, leading to a high inhalation risk for exposed people.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, in some indoor environments, such as buoyancy‐driven ventilated spaces with DV, 31,32 UFAD, 33,34 and/or NV, 35,36 the air temperature is vertically stratified because the low‐momentum air supply is attached to the floor, which is more likely to be seen in public places like shopping centers, railway waiting rooms, and the rebuilt Fangcang hospital. In such environments, the exhalation airflow and airborne pollutants were found to be easily trapped at a certain height and were able to penetrate a very long distance along the exhalation direction, which was referred to as the lock‐up phenomenon, as reported in previous studies 21,27,30,37,38 . Bjørn and Nielsen 17 observed that if the temperature gradient was sufficiently large, the lock‐up layer of the exhaled airborne pollutants could settle at breathing height, leading to a high inhalation risk for exposed people.…”
Section: Introductionmentioning
confidence: 71%
“…Bjørn and Nielsen 17 observed that if the temperature gradient was sufficiently large, the lock‐up layer of the exhaled airborne pollutants could settle at breathing height, leading to a high inhalation risk for exposed people. Liu et al 30 proposed a theoretical model to predict the exposure risk of susceptible people and found that the thermal stratification greatly weakened the decay of the exhaled pollutant concentration in the lock‐up layer, thereby increasing the cross‐infection range. This ventilation‐induced airborne transmission may be one important reason for the reported cluster outbreak cases in public places 27,39,40 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without a commonly recognized size threshold, splatters are generally considered to be large droplets and/or debris that is heavy enough to settle rapidly without spreading a long distance. Aerosols, on the other hand, are small droplets that can become smaller through evaporation and result in smaller residual aerosols (10 microns in size or smaller) that may stay suspended in air indefinitely since they are sufficiently small to overcome gravitational settling, especially in a thermally stratified indoor environment [32][33][34] . Although most of these residual aerosols are the result of the supplied cooling water, they can include patient saliva, dental plaque, calculus, and blood, which can be infectious to dental practitioners or other dental patients if a patient carries SARS-CoV-2 or other infectious agents.…”
Section: Introductionmentioning
confidence: 99%